2018
DOI: 10.1097/mjt.0000000000000643
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 3-Factor Versus 4-Factor Prothrombin Complex Concentrate With Regard to Warfarin Reversal, Blood Product Use, and Costs

Abstract: Four-PCC was more effective than 3-PCC with regard to INR reversal in patients taking warfarin, but blood product use was similar. Although 4-PCC is associated with increased reversal costs, it may be cost-effective in terms of INR reversal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 16 publications
2
34
0
Order By: Relevance
“…The proportion of patients who reached the goal INR was higher with PCC4 (87% vs. 31.6%, p < 0.001). Comparisons of PCC3 and PCC4 products for EWR have been done by others (17)(18)(19)(20)(21)(22)(23). Our study is similar to these other studies regarding retrospective design, PCC products compared, and the adult population.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The proportion of patients who reached the goal INR was higher with PCC4 (87% vs. 31.6%, p < 0.001). Comparisons of PCC3 and PCC4 products for EWR have been done by others (17)(18)(19)(20)(21)(22)(23). Our study is similar to these other studies regarding retrospective design, PCC products compared, and the adult population.…”
Section: Discussionsupporting
confidence: 81%
“…Given the compositional differences in the PCC products, it is important to know if there are differences in clinical response for effective and safe use of these products. Studies evaluating the comparative effects of PCC3 and PCC4 head-to-head for EWR with the outcome of INR lowering response and/or clinical outcomes are few (17)(18)(19)(20)(21)(22)(23). The inclusion criteria for these studies vary, but all were in adult patients needing reversal of warfarin for bleeding, surgical intervention, and/or trauma associated bleeding.…”
Section: Introductionmentioning
confidence: 99%
“…Four‐factor PCC contains thrombin, FVII, FIX, and FX, and protein C and S and should be given if reversal of VKA is required within 4‐6 hours in situations requiring emergency surgery or major hemorrhage. Three‐factor PCC contains significantly less FVII and reverses the INR to a lesser extent, so four‐factor PCC is to be preferred although there are a few countries that do not have access to four‐factor PCC . PCC is currently unlicensed in children and there is limited data upon its use.…”
Section: Anticoagulant Reversal In Emergency Surgerymentioning
confidence: 99%
“…Three-factor PCC contains significantly less FVII and reverses the INR to a lesser extent, so four-factor PCC is to be preferred although there are a few countries that do not have access to four-factor PCC. 28 PCC is currently unlicensed in children and there is limited data upon its use. There is also the potential concern that the risk of thrombosis can be increased after administration of PCC due to the patient's underlying prothrombotic state and the prothrombotic effect of PCC.…”
Section: Antithrombotics In Elective Surgerymentioning
confidence: 99%
“…7 A similar recent comparison in warfarin-anticoagulated patients revealed that 4-factor PCC was more effective in INR reversal (r 1.5) than 3-factor PCC (87.5% v 45.6%, p o 0.001). 8 While there was no difference in blood product transfusion, 4-factor PCC also was demonstrated to be a more costeffective option. These head-to-head comparisons alone should not be used to determine the one best option, but they should be used to emphasize the important relationship between Factor VII and INR values.…”
mentioning
confidence: 99%